New and traditional in wedding rites of the population of Western Kazakhstan (on example of Aktubinsk region) - Kalysh, A (Journal of history, 2020)
On the basis of field ethnographic materials the author, and special literature explores new and traditional wedding ceremonies in the population of Western Kazakhstan on the example of the Aktobe region. It is shown that this ritual organically combines the features of the past and present, is a common Kazakh and common Kazakhstan features, as well as some regional differences. For example, the Kazakhs marriage is carried out both in the form of a formal matchmaking, and by «kidnapping» or «escape» of the bride. The first form of marriage through matchmaking is more common among the East Slavic, mostly European and among other ethnic groups of Kazakhstan; second – among the Kazakhs, the Turkic ethnic groups or those who adhere to the rules of Islam.